21st Century Advances in Fluorescence Techniques to Characterize Glass‐Forming Polymers at the Nanoscale. Issue 3 (14th December 2017) - Burroughs, Mary J.; Christie, Dane; Gray, Laura A. G.; Chowdhury, Mithun; Priestley, Rodney D.
Abstract: Characterization of polymers at the nanometer‐length scale has become increasingly important with the growth and expansion of nanotechnology. Due to limitations of sensitivity and specificity that persist with traditional materials characterization techniques, there is a growing need to develop new tools to measure the properties of confined polymer systems. Within the past 20 years, fluorescence characterization techniques have emerged to address this challenge. This review focuses on the employment of fluorescence techniques such as temperature‐ and time‐dependent steady‐state intensity, fluorescence recovery after photobleaching, and nonradiative energy transfer to study polymer behavior at the nanoscale. Properties discussed include glass transition temperature, physical aging, diffusion and mobility, and mechanical response. Particular attention is given to the unique insight gained through these techniques as well as opportunities for future studies. The ability of fluorescence to obtain location‐ and component‐specific measurements with nanometer resolution for a variety of polymer chemistries and geometries on a bench‐top instrument provides a valuable contribution to the characterization and understanding of polymers at the nanoscale. Abstract : Fluorescence techniques present unique capabilities for characterization of glass‐forming polymers at the nanoscale. Advances in fluorescence over the past two decades have provided insight into the behavior of the glass transition temperature, physical aging, diffusion and mobility, and mechanical response in polymers confined to nanometer dimensions through sensitive, location‐specific measurements.